The first description of an apterous aphid morph of the family Canadaphididae (Hemiptera, Sternorrhyncha, Aphidomorpha) - Ogłaza, Bartosz; Wegierek, Piotr (Zootaxa, 2023)
The first apterous morph of the Canadaphididae family is described based on Canadian amber inclusions. On the basis of morphological features, it was assigned to the species Canadaphis carpenteri. For the first time, a fluorescence microscope was used to examine a representative of the Canadaphididae family, revealing previously unknown details.